2011
DOI: 10.1074/jbc.m110.171025
|View full text |Cite
|
Sign up to set email alerts
|

UNC93B1 Is Essential for TLR11 Activation and IL-12-dependent Host Resistance to Toxoplasma gondii

Abstract: Toll-like receptor (TLR) activation relies on biochemical recognition of microbial molecules and localization of the TLR within specific cellular compartments. Cell surface TLRs largely recognize bacterial membrane components, and intracellular TLRs are exclusively involved in sensing nucleic acids. Here we show that TLR11, an innate sensor for the Toxoplasma protein profilin, is an intracellular receptor that resides in the endoplasmic reticulum. The 12 membrane-spanning endoplasmic reticulum-resident protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 48 publications
0
105
0
2
Order By: Relevance
“…IL-12-independent functions of MyD88 are also supported by the inability of recombinant IL-12 to rescue T. gondii-infected MyD88 −/− mice (16). Although this treatment protects DC-specific MyD88-deficient mice as well as 3d mice with impaired functions in all endosomal TLRs (20), exogenous IL-12 fails to protect complete MyD88-deficient mice from T. gondii (16,21). In this study, we established that IL-1R-mediated MyD88 activation cooperates with TNF to regulate IL-12-independent IFN-γ.…”
Section: Treatment Of Neutrophil-depleted Tlr11mentioning
confidence: 95%
See 2 more Smart Citations
“…IL-12-independent functions of MyD88 are also supported by the inability of recombinant IL-12 to rescue T. gondii-infected MyD88 −/− mice (16). Although this treatment protects DC-specific MyD88-deficient mice as well as 3d mice with impaired functions in all endosomal TLRs (20), exogenous IL-12 fails to protect complete MyD88-deficient mice from T. gondii (16,21). In this study, we established that IL-1R-mediated MyD88 activation cooperates with TNF to regulate IL-12-independent IFN-γ.…”
Section: Treatment Of Neutrophil-depleted Tlr11mentioning
confidence: 95%
“…IFN-γ production from NK and T cells is regulated by TLR11, UNC93B1, and TLR12-dependent induction of interleukin-12 (IL-12) (15,16,21,23). The appearance of IFN-γ + neutrophils in the absence of TLR11 or UNC93B1 raised the question of whether IL-12 plays a role in triggering a neutrophilderived IFN-γ response.…”
Section: Neutrophils Produce Ifn-γ In Response To T Gondii and S Tymentioning
confidence: 99%
See 1 more Smart Citation
“…The persistence of infection requires not only the acute induction of immune mechanisms that control parasite hyperproliferation but also efficient dissemination of parasites into deep tissues, where they establish a chronic niche. A concept that is now gaining acceptance is that induction of proinflammatory cytokines essential for in vivo control of acute Toxoplasma infection involves intracellular signaling from endosomal and cytoplasmic pattern recognition receptors (PRRs) (22)(23)(24)(25)(26). Interestingly, the inflammatory cytokines IL-12 and IL-1β are both induced differentially by avirulent, but not virulent, Toxoplasma strains (9,27,28), presumably through intracellular activation of TLRs and other PRRs.…”
Section: Discussionmentioning
confidence: 99%
“…TLR is linked to infertility [33], pregnancy disorders, and placental dysfunction [34]. In toxoplasmosis TLR2, TLR4, TLR9, and TLR11 have been found important for recognition of ligands expressed by T. gondii [1,[35][36][37]. Andrade et al [38] have demonstrated TLR7 and TLR9 sense T. gondii-associated nucleic acids (DNA or RNA) while TLR11 and TLR12 sense Toxoplasma profiling.…”
Section: Importance Of Human Genetic Variation For Toxoplasmosis Infementioning
confidence: 99%